Governing Suburbia through regionalized land-use planning? Experiences from the Greater Frankfurt region. (February 2020) - Monstadt, Jochen; Meilinger, Valentin
Highlights: Describes the shifts in spatial planning and regional governance to contain urban sprawl in the Greater Frankfurt Area. Explores the heterogeneous suburbanization patterns in light of their political economies. Explains contradiction of rigid spatial planning system vis-à-vis peripheral settlement growth and socio-spatial polarization. Critically assesses the effectiveness of regionalized land-use planning and points to regional reform. Explains regional suburbanization through key modalities of suburban governance. Abstract: This paper explores the case of peripheral settlement growth in the Greater Frankfurt (Main) region within current debates on global suburbanization. Within Germany's sophisticated spatial planning regime, Greater Frankfurt's system of regionalized land-use planning marks an ambitious initiative to contain urban sprawl. Nonetheless, expansive peripheral settlement growth, and socio-spatial polarization remain distinct characteristics of the booming region. Analyzing state regulation vis-à-vis dynamics of capitalist urbanization and private authoritarianism, we decipher the complex governance arrangements producing this, at first sight, contradictory simultaneity. We uncover the rationales of local growth politics of autonomous municipalities and the region's multiplied institutional fragmentation that undermine planning ambitions to contain suburban growth. We conclude by critically assessing the political economies of suburbanization in Greater Frankfurt and point to prospects for regional reform.